(untitled) (Annals of Medical Research, 2021)
Aim: Ibuprofen is an older agent, but its intravenous form is a very new drug. The aim of this study was to investigate whether intravenous form of ibuprofen has protective effect against renal ischemia reperfusion injury at two different doses such as 10-30 mg/kg.Material and Methods: Thirty-two Wistar Albino type female rats were divided into 4 groups as sham, control, IBU-10, IBU-30. In the control group, 60 minutes renal ischemia and 60 minutes reperfusion were performed. In the ibuprofen groups, at the 45th minute of ischemia, ibuprofen was administered in different doses at 10 mg/kg and 30 mg/kg through intraperitoneally. After 60 minutes of ischemia, the clamps were opened. Renal tissue and blood samples were collected from the rats at the end of the reperfusion period. Serum TAS, TOS and prolidase enzyme levels were analyzed in plasma samples. Both histopathological and biochemical evaluations were performed with kidney tissue. Results: In the groups given intravenous ibuprofen, less cellular damage was always detected. Cellular damage indicators were significantly lower in the treated rats than in the control group. Serum and tissue prolidase values were different between groups (p0.001, p0.001). Serum TAS and TOS levels were also different between groups (p=0.001, p=0.003). Serum OSI levels were also different between groups (p=0.017).Conclusion: The biochemical and pathological results obtained in our study suggest that intravenous ibuprofen, has a protective effect against kidney damage. We believe that our study will shed light on future clinical prospective studies.